A influência do Programa Jovem Aprendiz na qualidade de vida de seus participantes: um estudo no Hospital São Paulo - Silva, Maria Jose Da [UNIFESP] (2020)
This study intends to investigate the Young Apprentice Program in the working environment of the Hospital São Paulo departing from the view of its participants, as well as its influence in the improvement of life of these young people. The method used is an exploratory cross-sectional research, with a qualitative and quantitative approach, which proposes to evaluate the influence of the professional education offered by the Young Apprentice Program on the young members, regarding also questions of life quality. The instruments used for the data collection were: socioeconomic questionnaire and demographic partner that were expressed in tables; WHOQOL-BREF quality of life questionnaire, ordered and accommodated in a spreadsheet in Excel® software version 2010; semi-structured interview script, recorded in audio and transcribed in full. The methodological resources were analyzed according to the themes in the light of the theoretical reference, based on the specific objectives of the research and the nucleiconducting the analysis. In general, for young people, participation in the Young Apprentice Program meant an opportunity for personal evolution as a life experience and possibility of overcoming, as well as the possibility of independence, correction of directions and perspectives of professional growth and approach to the labor market.